Exploring gender differences in labor markets from the perspective of the task based approach - Brambilla, Irene; César, Andrés; Falcone, Guillermo; Gasparini, Leonardo (Estudios de Economía, 2023)
Using households survey microdata from Argentina, Brazil, Chile, Colombia, Mexico and Peru, we characterize changes in employment and wages between the mid-2000s and the late-2010s emphasizing the gender dimension from the viewpoint of the task-based approach. We employ surveys from PIAAC-OECD to study the task content of jobs and create an index of routine task content (RTC) of occupations. We document five facts: (i) The proportion of routine tasks is currently higher for women than for men. (ii) The employment structure is considerably more biased towards high-RTC jobs in Latin America than in OECD countries, for both genders. (iii) There was an increase in the employment participation of low-RTC jobs during the period under study, mainly driven by movements in the occupational structure of women, especially the young and middle-aged. (iv) Wage gains were relatively higher in high-RTC occupations, with this pattern more pronounced for men than for women. (v) While there was a modest reduction in the gender wage gap, the decline was stronger in computer-intensive occupations.